World Water Assessment Program case study, Ruhuna basins, Sri Lanka - Imbulana, K.A.U.S.; Droogers, Peter; Makin, Ian W. (International Water Management Institute, 2004)
The "Ruhuna Basins" defined for this case study encompass three of the main rivers that flow through ancient Ruhuna, including the longest and most important river in the region, Walawe. The Ruhuna basins are important in the broader Sri Lankan context, the basin being the location of a major hydropower plant, irrigation schemes that make a significant contribution to national food production, and important nature reserves. However, even before the proposed development begins to be implemented, the basins are experiencing major water resources problems, clearly demonstrated by the recent drought that led to reduction of water supplies to agriculture, insufficient domestic water supply, and which contributed to nationwide power cuts upto 8 hours a day. These challenging issues motivated the Government of Sri Lanka to select the cluster of three important rivers, Walawe, Menik and Kirindi, and the smaller basins confined by them as the area for the case study for the World Water Assessment Program.